Biogenic synthesis of titanium nanoparticles by Streptomyces rubrolavendulae for sustainable management of Icerya aegyptiaca (Douglas) - Enayat M. Elqady; Eman El-said; Asmaa A. Tharwat; Lina A. Abou El-Khashab; Inas M. Y. Mostafa; Fatma Z. Hamed; Wesam M. Morsi; Mohamed M. Rezk; Inas M. Abou El-Enain (Scientific Reports)
Abstract Biosynthesized nanoparticles have a variety of applications, and microorganisms are considered one of the most ideal sources for the synthesis of green nanoparticles. Icerya aegyptiaca (Douglas) is a pest that has many generations per year and can affect 123 plant species from 49 families by absorbing sap from bark, forming honeydew, causing sooty mold, and attracting invasive ant species, leading to significant agricultural losses. The purpose of this work was to synthesize titanium dioxide nanoparticles (TiO2-NPs) from marine actinobacteria and evaluate their insecticidal effects on Icerya aegyptiaca (Hemiptera: Monophlebidae), in addition to explaining their effects on protein electrophoresis analysis of SDS‒PAGE proteins from control and treated insects after 24, 72 and 120 h of exposure. In all, seven actinobacterial isolates, the most potent of which has the potential to produce titanium hydroxide-based nanoparticles (TiO2-NP2), have DNA sequences that are 99.9% like those of Streptomyces rubrolavendulae (MCN2) according to nucleotide alignment and a phylogenetic tree. The produced TiO2-NPs were verified by UV examination and characterized by FT-IR, XRD, TEM, EDX, and DLS analyses. Toxicological results revealed that TiO2-NPs have insecticidal effects and high mortality rates reaching 55, 62.5, 80 and 95% at TiO2-NPs dose 120,250,500 and 1000 ppm respectively. Compared with the control, TiO2-NP spraying caused changes in the protein pattern of I. aegyptiaca, as indicated by the disappearance of normal bands and the appearance of other bands, as well as quantitative and qualitative changes in protein content after 24, 72 and 120 h of exposure. The application of TiO2-NPs by MNC2 offers a new alternative strategy to control I. aegyptiaca and is considered a modern approach to nanotechnology.